디지털 자산의 포트폴리오 분산투자 효과 - 김선웅(Sun-Woong Kim) (디지털콘텐츠학회논문지, 2021)
본 연구는 최근 투자자와 언론 모두에서 큰 관심 영역이 된 비트코인 등의 디지털 자산을 국내 증권시장의 주식, 채권 등의 전통적 자산으로 구성된 포트폴리오에 포함하는 경우 얻을 수 있는 분산투자 효과를 검증하였다. 2011년 1월부터 2021년 4월까지의 기간에서 주식, 채권, 금으로 구성된 전통적 자산 포트폴리오와 비트코인까지 확장된 포트폴리오를 분석하였다. 실증 분석 결과는 다음과 같다. 첫째, 비트코인을 포함하는 포트폴리오는 높은 위험과 수익률을 보여주었다. 둘째, 비트코인을 포함하는 포트폴리오의 성과에서 위험과 수익을 고려하는 성과 지표가 더 높게 나타남에 따라 국내 증권시장에도 비트코인의 분산투자 효과가 존재한다. 셋째, 벤치마크 전략 대비 제안된 자산 배분 전략들의 성과 지표가 더 높게 나타났다. 실증 분석 결과, 국내 증권시장에서도 디지털 자산의 포트폴리오 분산투자 효과가 존재함을 처음으로 밝혔다는 점에서 본 연구의 학술적 의미를 찾을 수 있으며 동시에 국내 증권시장 참여자들에게는 비트코인 등의 디지털 자산으로 포트폴리오를 확대하면 전통적인 자산 포트폴리오의 성과를 개선할 수 있음을 보여주었다. This study verifies the diversification effect when digital assets such as Bitcoin, which have recently become a major area of interest for both investors and media, are included in a portfolio of traditional assets such as stocks and bonds in the domestic securities market. Traditional portfolio with stock, bond, and gold and expanded portfolio including Bitcoin were analyzed from January 2011 to April 2021. The empirical results are as follows. First, Bitcoin portfolios showed high risk and return. Second, the portfolio performance indexes, which consider risk and return, were higher in Bitcoin portfolios, indicating that Bitcoin’s diversification effect exists in the domestic market. Third, the performance indexes of the proposed asset allocation strategies compared to the benchmark strategy were higher. The empirical analysis of the study found academic significance in that the domestic market also has a portfolio diversification effect, and showed that market participants can improve the performance of traditional assets portfolios by using Bitcoin. KCI Citation Count: 5